1995
DOI: 10.1021/j100007a013
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibrium in (Cyclopropylmethyl)acetylene: a Microwave Spectroscopy and ab Initio Calculation Study

Abstract: The microwave spectrum of (cyclopropylmethy1)acetylene (a newly prepared compound) was investigated in the frequency range 28-40 GHz. Both gauche and cis conformers were observed, the latter being 64 f 30 cm-' lower in energy. The geometries of these conformers were obtained combining the ab initio and microwave spectroscopy results. A large-amplitude motion (the methylacetylene group torsion) was studied by assigning the rotational spectra of several torsionally excited states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 8 publications
6
29
3
Order By: Relevance
“…This value should be near the value for the gas because both conformers have similar sizes and polarities. The value of the enthalpy implies at room temperature a gas-phase equilibrium mixture of 48% cis conformer and 52% gauche rotamer, which is a slightly smaller amount of the gauche conformer than previously suggested from the microwave data 3 Temperature and Intensity Ratios from Conformational Study of Cyclopropylmethylacetylene T (°C)1000/ T (K) I 1052 / I 1045 I 1021 / I 1019 I 848 / I 828 I 575 / I 502 −55 4.58 0.758 0.778 0.236 −60 4.69 0.786 0.826 0.850 0.233 −65 4.80 0.786 0.856 0.876 0.241 −70 4.92 0.788 0.881 0.890 −75 5.05 0.806 0.874 0.886 0.241 −80 5.18 0.817 0.920 0.898 0.268 −85 5.31 0.878 0.955 0.906 0.288 −90 5.46 0.894 0.995 0.922 0.308 −95 5.61 0.908 1.008 0.970 0.300 −100 5.78 0.932 1.029 1.033 Δ H a (cm -1 ) 124 ± 10 157 ± 10 103 ± 15 203 ± 30 a Average value of Δ H is 147 ± 14 cm -1 (1.76 ± 0.16 kJ/mol) with the cis conformer the more stable form. …”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…This value should be near the value for the gas because both conformers have similar sizes and polarities. The value of the enthalpy implies at room temperature a gas-phase equilibrium mixture of 48% cis conformer and 52% gauche rotamer, which is a slightly smaller amount of the gauche conformer than previously suggested from the microwave data 3 Temperature and Intensity Ratios from Conformational Study of Cyclopropylmethylacetylene T (°C)1000/ T (K) I 1052 / I 1045 I 1021 / I 1019 I 848 / I 828 I 575 / I 502 −55 4.58 0.758 0.778 0.236 −60 4.69 0.786 0.826 0.850 0.233 −65 4.80 0.786 0.856 0.876 0.241 −70 4.92 0.788 0.881 0.890 −75 5.05 0.806 0.874 0.886 0.241 −80 5.18 0.817 0.920 0.898 0.268 −85 5.31 0.878 0.955 0.906 0.288 −90 5.46 0.894 0.995 0.922 0.308 −95 5.61 0.908 1.008 0.970 0.300 −100 5.78 0.932 1.029 1.033 Δ H a (cm -1 ) 124 ± 10 157 ± 10 103 ± 15 203 ± 30 a Average value of Δ H is 147 ± 14 cm -1 (1.76 ± 0.16 kJ/mol) with the cis conformer the more stable form. …”
Section: Methodsmentioning
confidence: 90%
“…As a continuation of our conformational studies of these three-membered rings, we have investigated the vibrational spectrum of cyclopropylmethylacetylene, c -C 3 H 5 CH 2 CCH. There has been a recent conformational study of this molecule from a microwave investigation and ab initio calculations . It was concluded that the cis conformer was more stable than the gauche rotamer by 64 ± 30 cm -1 (0.77 ± 0.36 kJ/mol) from relative intensity measurements of the microwave transitions .…”
Section: Introductionmentioning
confidence: 99%
“…However, later studies [4][5][6] conclusively showed that the predominant form was the gauche conformer and from variable temperature studies of the infrared spectra of xenon solutions [7] the enthalpy difference was determined to be 274 ± 21 cm À1 (3.28 ± 0.25 kJ mol À1 ) with only 12% of the cis form present at room temperature. With other X substituents such as cyano ACN [8,9], and ethynyl AC"CH [10,11] groups the percent of the gauche form present at ambient temperature dropped to 72% and 52%, respectively. Some investigators [10] concluded that the abundance of the cis conformers parallels the increase of the electronegativity [12] of the substituents for the monosubstituted methylcyclopropane molecules.…”
Section: Introductionmentioning
confidence: 98%
“…With other X substituents such as cyano ACN [8,9], and ethynyl AC"CH [10,11] groups the percent of the gauche form present at ambient temperature dropped to 72% and 52%, respectively. Some investigators [10] concluded that the abundance of the cis conformers parallels the increase of the electronegativity [12] of the substituents for the monosubstituted methylcyclopropane molecules. However, more recent conformational studies [13] of fluoromethylcyclopropane where only 12% of the cis form was found at ambient temperature indicate that the electronegativity can not be the dominant factor controlling the abundance of the cis form.…”
Section: Introductionmentioning
confidence: 98%
“…Initially, it was proposed [1] that the electronegativity of the substituent has the most pronounced effect on the relative amounts of the conformational isomers present since the substitution of the ethynyl and cyano-groups had a relatively larger amount of the cis (syn) form present compared to the amount of the gauche conformers. These groups have considerably larger electronegativities [2] i.e.…”
Section: Introductionmentioning
confidence: 99%